Respuesta :
First of all, the answer is x=0. Second, lets go through the steps
First, Simplify both sides of the equation
Second Add 6x to Both Sides
Third, add 4 to both sides
Fourth, Divide both sides by 11.
You get 0/11, so X=0
Hope this helps!
First, Simplify both sides of the equation
Second Add 6x to Both Sides
Third, add 4 to both sides
Fourth, Divide both sides by 11.
You get 0/11, so X=0
Hope this helps!
5x - 4 = -2(3x + 2) |use distributive property: a(b + c) = ab + ac
5x - 4 = -2(3x) - 2(2)
5x - 4 = -6x - 4 |add 4 to both sides
5x = -6x |add 6x to both sides
11x = 0 |divide both sides by 11
x = 0
5x - 4 = -2(3x) - 2(2)
5x - 4 = -6x - 4 |add 4 to both sides
5x = -6x |add 6x to both sides
11x = 0 |divide both sides by 11
x = 0